2017
DOI: 10.1111/inm.12329
|View full text |Cite
|
Sign up to set email alerts
|

Predicting psychological distress of informal carers of individuals with major depression or bipolar disorder

Abstract: Caring for someone with a mental illness is associated with high levels of burden and psychological distress. Understanding these factors could be important to prevent the development of physical and mental health problems in carers. The purpose of the present study was to determine the contribution of coping styles and social support in predicting the psychological distress reported by informal carers (IC) of individuals with major depression or bipolar disorder. IC (n = 72) of adults with a diagnosed depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“… 4 These caregivers seem to have an emotional overinvolvement similar to that of family members of patients with schizophrenia, 5 , 6 reporting high levels of subjective and objective burden, restrictions in social life, a high risk to develop depressive or anxiety symptoms, financial and working difficulties, general global health problems, and a reduced quality of life. 7 12 Moreover, caregivers often report feelings of powerlessness, hopelessness, and inability to change the situation. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“… 4 These caregivers seem to have an emotional overinvolvement similar to that of family members of patients with schizophrenia, 5 , 6 reporting high levels of subjective and objective burden, restrictions in social life, a high risk to develop depressive or anxiety symptoms, financial and working difficulties, general global health problems, and a reduced quality of life. 7 12 Moreover, caregivers often report feelings of powerlessness, hopelessness, and inability to change the situation. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Stress process models explain carer outcomes in response to caregiving stress [ 27 ] and propose that social support and coping strategies are important moderators of IC adjustment across carer populations [ 28 33 ]. There is evidence of applicability of the model in ICs of people with personality disorders [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 36 ). Maladaptive coping strategies predicted psychological distress in ICs of people with eating disorders [ 37 ] and affective disorders [ 33 ]. Avoidance coping strategies correlated with burden in ICs of people with schizophrenia and bipolar affective disorder [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…But what is evidenced in this study, and is shown in Table 4, is a long list of participation challenges that have also been identified in the literature (see Chapter 2 herein and, Storm & Edwards, 2012). These challenges identify that implementing participation policy is 'easier said than done' and include competing priorities, managing mental illness risk and safety, high workloads, high demand for services (DoH, 2013); the non-linear path of mental health recovery (Anthony, 1993;Slade, 2009); the capacity to participate; human resource challenges including, managing the consumer workforce in recovery, carers experiencing fluctuating degrees of carer stress (Wingrove & Rickwood, 2019) and carer burden (Wasley & Eden, 2018); and a person's right not to participate. Given these individual, social, structural and systemic challenges, what becomes evident in this study is that a tension exists between participation theory and practice.…”
Section: Participation Practicesmentioning
confidence: 99%